Wireless Networks and Computational Intelligence 6th International Conference on Information Processing, ICIP 2012, Bangalore, India, August 10-12, 2012. Proceedings - Venugopal, K. R.; Patnaik, L. M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 6th International Conference on Information Processing, ICIP 2012, held in Bangalore, India, in August 2012. The 75 revised full papers presented were carefully reviewed and selected from 380 submissions. The papers are organized in topical sections on wireless networks; image processing; pattern recognition and classification; computer architecture and distributed computing; software engineering, information technology and optimization techniques; data mining techniques; computer networks and network security.
Keywords: Computer science; Computer Communication Networks; Data protection; Information storage and retrieval systems; Artificial intelligence; Computer vision; Computer Science; Computer Communication Networks; Computer Imaging, Vision, Pattern Recognition and Graphics; Information Storage and Retrieval; Systems and Data Security; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).